2011
DOI: 10.1101/lm.2245911
|View full text |Cite
|
Sign up to set email alerts
|

A protein synthesis and nitric oxide-dependent presynaptic enhancement in persistent forms of long-term potentiation

Abstract: Long-term potentiation (LTP) is an important process underlying learning and memory in the brain. At CA3-CA1 synapses in the hippocampus, three discrete forms of LTP (LTP1, 2, and 3) can be differentiated on the basis of maintenance and induction mechanisms. However, the relative roles of pre-and post-synaptic expression mechanisms in LTP1, 2, and 3 are unknown. Neurotransmitter release in the expression of LTP1, 2, and 3 was measured via FM 1 -43 destaining from CA3 terminals in hippocampal slices from male W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 88 publications
(117 reference statements)
6
22
0
Order By: Relevance
“…After challenging with glycine-induced synaptic potentiation (Gly-SP) protocol (Fig. 3A) [22], the rate of FM 4-64 destaining, which is known to be a reliable indicator for presynaptic release probability [21], [23], was accelerated, indicating that the presynaptic functions were enhanced by the Gly-SP(Fig. S5).…”
Section: Resultsmentioning
confidence: 99%
“…After challenging with glycine-induced synaptic potentiation (Gly-SP) protocol (Fig. 3A) [22], the rate of FM 4-64 destaining, which is known to be a reliable indicator for presynaptic release probability [21], [23], was accelerated, indicating that the presynaptic functions were enhanced by the Gly-SP(Fig. S5).…”
Section: Resultsmentioning
confidence: 99%
“…In addition it has been proposed that the properties of LTP change over time. For instance, a widely held model suggests that at some point after the induction of LTP (>1 hour), protein synthesis is required to maintain the potentiation (Johnstone and Raymond, 2011; Reymann and Frey, 2007; Schuman et al, 2006). However it should be noted that, although rarely cited, there have been a number of well controlled studies that have failed to find any dependence of LTP on protein synthesis up to 8 hours after the induction (e.g., (Abbas et al, 2009; Villers et al, 2012).…”
Section: Multiple Forms Of Ltpmentioning
confidence: 99%
“…For instance, protein synthesis is thought to be required for the maintenance of LTP at some point (approx. 1 h) following induction [8][9][10]. Although rarely cited, there are also a number of very well-controlled studies that have found no effect of protein synthesis inhibition for up to 8 h following the tetanus [11,12].…”
Section: Multiple Forms Of Long-term Potentiationmentioning
confidence: 99%